Unexpected mixed-mode transmission and moderate genetic regulation of Symbiodinium communities in a brooding coral. (December 2018) - Quigley, Kate; Warner, Patricia; Bay, Line; Willis, Bette
Abstract Determining the extent to whichSymbiodinium communities in corals are inherited versus environmentally acquired is fundamental to understanding coral resilience and to predicting coral responses to stressors like warming oceans that disrupt this critical endosymbiosis. We examined the fidelity with whichSymbiodinium communities in the brooding coralSeriatopora hystrix are vertically transmitted and the extent to which communities are genetically regulated, by genotyping the symbiont communities within 60 larvae and their parents (9 maternal and 45 paternal colonies) using high-throughput sequencing of the ITS2 locus. Unexpectedly, Symbiodinium communities associated with brooded larvae were distinct from those within parent colonies, including the presence of types not detected in adults. Bayesian heritability (h 2 ) analysis revealed that 33% of variability in larvalSymbiodinium communities was genetically controlled. Results highlight flexibility in the establishment of larval symbiont communities and demonstrate that symbiont transmission is not exclusively vertical in brooding corals. Instead, we show thatSymbiodinium transmission inS. hystrix involves a mixed-mode strategy, similar to many terrestrial invertebrate symbioses. Also, variation in the abundances of commonSymbiodinium types among adult corals suggests that microhabitat differences influence the structure ofin hospite Symbiodinium communities. Partial genetic regulation coupled with flexibility in the environmentally acquired component ofSymbiodinium communities implies that corals with vertical transmission, likeS. hystrix, may be more resilient to environmental change than previously thought.